2016
DOI: 10.2334/josnusd.16-0251
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional changes in the temporomandibular joint after maxillary protraction in children with skeletal Class III malocclusion

Abstract: We evaluated 3-dimensional changes in the temporomandibular joints of children with skeletal Class III malocclusion and maxillary deficiency after facemask therapy for maxillary protraction. Eighteen children with anterior crossbite and a Class III molar relationship underwent facemask therapy for maxillary protraction, after which they exhibited positive overjet and a Class II molar relationship. Three-dimensional cone-beam computed tomography images of the patients were obtained before (T1) and after (T2) fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
22
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 20 publications
4
22
0
7
Order By: Relevance
“…According to the GRADE quality analysis, the three RCTs [ 26 , 46 , 49 , 56 ] were graded as high value of evidence, seven studies [ 47 , 48 , 50 53 , 55 , 59 ] were graded as moderate value of evidence, and three studies [ 54 , 57 , 58 ] were graded as low value of evidence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the GRADE quality analysis, the three RCTs [ 26 , 46 , 49 , 56 ] were graded as high value of evidence, seven studies [ 47 , 48 , 50 53 , 55 , 59 ] were graded as moderate value of evidence, and three studies [ 54 , 57 , 58 ] were graded as low value of evidence.…”
Section: Resultsmentioning
confidence: 99%
“…3 ). All the before-after studies [ 54 , 57 , 58 ] with no control group showed no description of the derivation of the control group, and lost comparability of participants between treatment and control groups (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crianças com dentes desalinhados podem necessitar de tratamento ortodôntico para melhorar a função, estética e saúde bucal (de Sousa et al, 2016). A maloclusão significa o desvio da oclusão normal dos dentes, caracterizada por padrões neuromusculares atípicos originados por hábitos deletérios, alterando a posição dos dentes e promovendo alterações no sistema estomatognático (Lee et al, 2016;Masood et al, 2017;Moreau et al, 2017).…”
unclassified